2010
DOI: 10.1371/journal.pbio.1000537
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Organ Shape and Tissue Polarity

Abstract: A combination of experimental analysis and mathematical modelling shows how the genetic control of tissue polarity plays a fundamental role in the development and evolution of form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
138
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(142 citation statements)
references
References 44 publications
4
138
0
Order By: Relevance
“…They showed that the difference between these is often not trivial, and even with very simple shapes it is not intuitive how to go from genes to final form. In their simulations (1,(3)(4)(5), plant tissue is modeled as a continuous 2D sheet of material, with any effects from the underlying cellular structure homogenized into the material parameters. Here we have extended this paradigm by considering the effect of the full 3D cellular geometry and topology on cell expansion, both in cellular plant tissues obtained from confocal images and in computer-generated templates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the difference between these is often not trivial, and even with very simple shapes it is not intuitive how to go from genes to final form. In their simulations (1,(3)(4)(5), plant tissue is modeled as a continuous 2D sheet of material, with any effects from the underlying cellular structure homogenized into the material parameters. Here we have extended this paradigm by considering the effect of the full 3D cellular geometry and topology on cell expansion, both in cellular plant tissues obtained from confocal images and in computer-generated templates.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are few studies that link genes directly with shape change in a mechanistic way (3)(4)(5). In plants, where cells do not move, nearly all shape change and morphogenesis occur through the tightly regulated control over the mechanical properties of the cell wall.…”
mentioning
confidence: 99%
“…4 D and E and 5A), restoring cell packing. In contrast, the orientation of divisions will tend to alternate in nonstretched monolayers, promoting isotropic monolayer growth, as commonly observed in proliferating plant tissues, where no neighbor exchange occurs (28).…”
Section: Discussionmentioning
confidence: 98%
“…However, the mechanisms coordinating cell proliferation and cell size during organ growth remain poorly understood (Johnston and Gallant 2002). Due to the simpler planar structures of their organs, such as leaves and petals, and the absence of cell movement due to rigid cell walls, plants have some experimental advantages for studying organ growth (Green et al 2010).…”
mentioning
confidence: 99%